Odpowiedzi

Najlepsza Odpowiedź!
2009-12-16T17:20:45+01:00
A)3x + 6x - 4y - 2x + 3x + 9y =10x+5y
b) -3x-11y -6y - 3 =-3x-17y-3
c) (x-4)+ 6(3x - 2)- 5(2 - x ) =x-4+18x-12-10+x=20x-26
d) -(-4 - y) + 7(y - 7)-(-3)(2y - 6) =4+y+7y-49+6y-18=14y-63
2 5 2
2009-12-16T17:23:30+01:00
A)3x + 6x - 4y - 2x + 3x + 9y = 10x + 5y

b) -3x-11y + (-6)y - 3 = -3x - 17y - 3

c) (x-4)+ 6(3x - 2)- 5(2 - x ) = (x-4) + 18x - 12 - 10 +5x =24x - 26

d) -(-4 - y) + 7(y - 7)-(-3)(2y - 6) = 4 +y + 7y + 49 - [(-6y) + 18) = 53 + 8y + 6y - 18 = 35 + 14y
2 4 2
2009-12-16T17:26:54+01:00
A)3x+6x-4y-2x+3x+9y=10x-5y
b)-3x-11y+(6)y-3=-3x-22-3
c)(x-4)+6(3x-2)-5(2-x)=-3x+18x-5x-4+12-10
d)-(-4-y)+7(y-7)-(3)(2y-6)=3y-6y+2y-4+14-6